2015
DOI: 10.1155/2015/430525
|View full text |Cite
|
Sign up to set email alerts
|

Resistance to P. brasiliensis Experimental Infection of Inbred Mice Is Associated with an Efficient Neutrophil Mobilization and Activation by Mediators of Inflammation

Abstract: Paracoccidioidomycosis (PCM) is a systemic fungal infection, endemic in Brazil, that leads to severe morbidity and even mortality if not correctly treated. Patients may respond differently to PCM depending on the pattern of the acquired immune response developed. The onset of protective immune response is notably mediated by neutrophils (PMN) that play an important role through directly killing the fungi and also by interacting with other cell types to modulate the acquired protective immune response that may … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
2
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 36 publications
1
2
0
3
Order By: Relevance
“…Pina et al (2006) observed a significant difference, in the role of neutrophils, between resistant and susceptible mice; thus, in susceptible mice, these phagocytic cells have low fungicidal activity, but in contrast, neutrophils from resistant mice are more abundant in the lesion areas and efficient to control infection. Similar results were obtained by Sperandio et al (2015), who using resistant and susceptible mice to PCM showed that in susceptible mice, the infection was able to disseminate to their bone marrow, impairing the production and maturation of neutrophils, which is different from what was observed in resistant mice.…”
Section: Paracoccidioidomycosissupporting
confidence: 78%
See 1 more Smart Citation
“…Pina et al (2006) observed a significant difference, in the role of neutrophils, between resistant and susceptible mice; thus, in susceptible mice, these phagocytic cells have low fungicidal activity, but in contrast, neutrophils from resistant mice are more abundant in the lesion areas and efficient to control infection. Similar results were obtained by Sperandio et al (2015), who using resistant and susceptible mice to PCM showed that in susceptible mice, the infection was able to disseminate to their bone marrow, impairing the production and maturation of neutrophils, which is different from what was observed in resistant mice.…”
Section: Paracoccidioidomycosissupporting
confidence: 78%
“…• IL-8 production inhibits apoptosis and allows fungal replication • Paracoccin induces: IL-8, IL-1b, ROS production, DNA release and inhibit apoptosis • Phagocytic cells primed with IFN-g, IL-1b, GM-CSF, TNF-a, and IL-15 exhibit antifungal activity and trigger respiratory burst • Host genetic background influences their immunoregulatory functions • Puerta-Arias et al, 2018• Mejıá et al, 2015Della-Coletta et al, 2015;Bachiega et al, 2016• Acorci-Valeŕio et al, 2010Balderramas et al, 2014;Gardizani et al, 2019• Balderramas et al, 2014• Acorci et al, 2008• Ricci-Azevedo et al, 2018• Kurita et al, 2000Tavian et al, 2007;Rodrigues et al, 2007• Pina et al, 2006Sperandio et al, 2015 dermatitidis has been demonstrated (Brummer and Stevens, 1984;Brummer et al, 1986;Morrison et al, 1989), some reports have shown that neutrophils enhance and allow the replication of this fungal pathogen, a fact that was associated with an exacerbation of the infection by accumulation and death of neutrophils in the tissue lesions (Brummer and Stevens, 1983). In this sense, the presence of a fungal chemotactic factor in serum-free culture filtrated of B. dermatitidis has been demonstrated (Sixbey et al, 1979;Thurmond and Mitchell, 1984).…”
Section: Histoplasmosismentioning
confidence: 99%
“…Apesar dos camundongos suscetíveis produzirem maior número de neutrófilos, esses foram menos eficazes em matar os fungos. As citocinas inflamatórias foram mais pronunciadas em camundongos resistentes, o que favorece a resistência aumentada do PCM (SPERANDIO et al, 2015).…”
Section: Imunologia Na Pcmunclassified
“…Assim, os neutrófilos de resistentes ligam-se mais rapidamente às leveduras de P. brasiliensis e dirigem a resposta adquirida para o padrão protetor Th1. Mais uma vez, os neutrófilos de camundongos suscetíveis foram menos competentes, tanto para internalizar as leveduras, como para modular a imunidade adquirida, que se dirigiu predominantemente para o padrão Th2, não protetor (Sperandio, Fernandes et al 2015).…”
Section: Consolidouunclassified